Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
The 15th Annual Meeting of the IEEE Lasers and Electro-Optics Society
DOI: 10.1109/leos.2002.1134078
|View full text |Cite
|
Sign up to set email alerts
|

Laser-activated shape memory polymer microactuators for treating stroke

Abstract: We present interventional devices for treating ischemic stroke. The development and testing of two complementary devices is proposed a mechanical clot extraction system and a neurovascular stent. These devices are laser-activated shape memory polymer microactuators. Paper SummaryThe National Institutes of Health recently awarded a Bioengineering Research Partnership Grant for "Shape Memory Polymer Devices for Treating Stroke," which is a partnership between Lawrence Livermore National Laboratory (lead institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Athermally induced SMEs are caused by afebrile stimuli including light, electricity, magnetism, and solution-triggered actuation [58,69,76]. Wu et al [132] reported a biodegradable light-sensitive SMP consisting of block polyurethanes and pendant cinnamamide moieties.…”
Section: Athermally Induced Smesmentioning
confidence: 99%
“…Athermally induced SMEs are caused by afebrile stimuli including light, electricity, magnetism, and solution-triggered actuation [58,69,76]. Wu et al [132] reported a biodegradable light-sensitive SMP consisting of block polyurethanes and pendant cinnamamide moieties.…”
Section: Athermally Induced Smesmentioning
confidence: 99%
“…Narendra Kumar et al -eXPRESS Polymer Letters Vol.6, No.1 (2012) [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] …”
Section: Recovery By Environmental Heatingmentioning
confidence: 99%
“…Non contact initiation of SME was realized by irradiation with infrared light [29][30][31], applying radio-frequency (RF) [32], or an alternating magnetic field [4,10,[33][34][35][36]. The magnetically triggered SME can be characterized by a specific switching magnetic field strength H sw , which needs to be exceeded to induce the shape change [10].…”
mentioning
confidence: 99%
“…Different kinds of actuation methods are explored including heat [7], light [8,9], electricity [10,11], magnetic field [12,13], or solvent [14][15][16]. Electrically actuating SMPs by electrical resistive heating has been intensively studied.…”
Section: Introductionmentioning
confidence: 99%